The increasing geoeconomic usage of the Single Market for financial services - Lucia Quaglia; Amy Verdun (EconPol Forum, 2023)
The Single Market in financial services has increasingly been used for geoeconomic purposes, that range from incipient geoeconomic use to outward weaponization of the Single Market in finance. This geoeconomic usage can be illustrated in a few salient cases that involve the EU and other majorjurisdictions: (1) the post-2008 crisis transatlantic tug-of-war; (2) the Brexit negotiations; and (3) during the full-scale war in Ukraine. We adopt four metaphors to characterize the geoeconomic deployment of the Single Market and the EU's geoeconomic actorness. These are shield and sword; testudo; phalanx and scattered comman-dos. A mix of external and internal factors accounts for this pattern, for instance, changes to the internati-onal economic and political system as well as the development of the EU's ability to deploy its Single Market geoeconomically
Keywords: 330